The Effect of Job Appreciation and Perception on Organizational Commitment of State Senior High School Teachers in North Jakarta - Forman Setya Oktaviano; Ahmad Farhan Choirullah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Abstract: This research is made to determine (1) the influence between reward on perception of task teacher of state senior high school, (2) the influence between reward on organization commitment teacher of state senior high school, and (3) ) the influence between perception of task on organization commitment teacher of state senior high school. The research methodology that has been used was survey with path analysis technique in testing hypothesis. In this study, 96teacher of state senior high school have been used as a sample by using simple random sampling techniques (simple random sampling). This research conducted in North-Jakarta area. Based on the description of hypothesis test, the researches findings can be outlined as followed: (1) there is a positive direct effect of reward on perception of task; (2) there is a positive direct effect of reward on organization commitment; and (3) there is a positive direct effect of perception of task on organization commitment. The implication of this study is attempt of improving the organization commitment teacher of state senior high school that can be done through improve reward andperception of task. Keywords: organization commitment, reward, perception of task